Enhancing photoresponsivity of self-powered UV photodetectors based on electrochemically reduced TiO2 nanorods. Issue 116 (9th November 2015) - Yan, Pengli; Wu, Yihui; Liu, Guiji; Li, Ailong; Han, Hongxian; Feng, Zhaochi; Shi, Jingying; Gan, Yang; Li, Can
Abstract : Enhanced photoresponsivity of the R-NRA device is due to the enhancement of charge separation and transfer at the electrode/electrolyte interface. Abstract : Electrochemically reduced TiO2 nanorod arrays (R-NRAs) have been used for the first time to construct a self-powered, visible light blind ultraviolet (UV) photodetector. The fabricated R-NRAs device demonstrated superior photodetector performance with high photon-to-current efficiency of up to 22.5% at an applied bias of 0 V. The enhancement is attributed to a disordered surface layer which greatly improves the charge separation and transfer efficiency at the electrode/electrolyte interface.